RELAÇÃO ENTRE O GERENCIAMENTO DE RESULTADOS E O CUSTO DE CAPITAL: UMA ANÁLISE DAS EMPRESAS BRASILEIRAS DE CAPITAL ABERTO - FIRMINO, GIOVANA GARCIA (2017)
This study investigates the relationship between cost of capital and results management, a measure related to earnings quality in Brazilian publicly traded companies listed in B3 - Brasil Bolsa Balcão in the period from 2009 to 2016. The general objective of the present study is to analyze if there is a negative association between the management of results and the cost of capital and third parties. To measure the cost of equity, beta-β is used as a measure of the systematic risk, and as a measure of the cost of third-party capital, the variable Ki obtained from the ratio between financial expenses and the average of the onerous liabilities. As a proxy for results management, we use the Earning Quality variable derived from the measurement of results management by discretionary accruals obtained from three models for greater robustness of results: the Modified Jones model (1995), the model Kang and Sivaramakrishnan (1995) ) and the model McNilchols (2002). By means of a fixed effects panel and application of MQO models treated by means of robust standard errors in order to eliminate possible biases of heteroscedasticity and multicollinearity, EQ measurements were obtained for each of the proposed models and then they were tested in relation with the cost of capital and third parties by means of econometric models composed of control variables for the year 2016. The obtained results do not confirm the hypotheses proposed that there is a negative relation between EQ and cost of capital, contrary to previous works as that of Persakis and Iatridis (2015), opening the way for future research on the influences of the economic context on this relation.